The Development of Contextual Science Module for Middle School with Concept Mapping - Widya Nur Imami; Trapsilo Prihandono; Bambang Supriadi (Pancaran Pendidikan, 2017)
Research development designed to produce the product in the form of module science middle school based contextual accompanied concept mapping.This study attempts to: (1) described the validity of module, (2) described the effectiveness of module, and (3) described a response to module students. Design development use is 4-D. The research was conducted in SMP Negeri 2 Page .The result of research is: (1) validation experts and validation users are 80,5 % and 89,12 %. As a result validation, the research and users have produced module with the validity valid and worth trying out; (2) effectiveness module get result 93,6 %, the effectiveness of module high with the effectiveness very effective; and (3) response students are positive for every aspect response to the survey. The conclusion of analysis results in module science middle school based contextual accompanied concept mapping is valid and can be used in learning